Genetic predisposition to Behcet's disease mediated by a IL10RA enhancer polymorphism - Handan Tan; Zhenyu Zhong; Xiaojie Feng; Xiang Luo; Qingfeng Cao; Peizeng Yang (Heliyon)
Background: Several studies suggested the genetic association between IL10RA variants and susceptibility to Behcet's disease (BD). However, the precise mechanism of the association is still unknown. The purpose of this study was to investigate the mechanism underlying the genetic associations between IL10RA polymorphisms and the risk of BD. Methods: To analyse the genetic susceptibility to BD mediated by IL10RA causal polymorphisms, we performed a study on data from our previous genome-wide association studies (GWAS), the bioinformatic analysis of post-annotation of GWAS and relevant mechanism verification experiments, including chromatin immunoprecipitation, luciferase gene-reporter assay, electrophoretic mobility shift assays, and enzyme-linked immunosorbent assay. Results: Among 125 single nucleotide polymorphisms (SNPs) with P < 1 × 10-5 identified in our previous GWAS study on BD, rs4936415 (G/C) was predicted with the highest conserved score as an expression quantitative-trait-locus SNP for IL10RA in whole blood. There were H3K27ac and H3K4Me1 enhancer-specific enrichments around SNP rs4936415. Luciferase gene-reporter assays revealed that the rs4936415 G-allele construct showed a higher enhancer activity as compared to the empty and the C-allele construct. NF-κB1 was identified to bind the C-allele rather than the G-allele, although the enhancer SNP (rs4936415) region was found to control transcription factor binding sites. Interaction of C-allele and NF-κB1 gene construct resulted in an increased enhancer activity. BD patients showed a significantly lower serum level of the IL-10Rα. Conclusions: This study identified a single functional causal SNP, rs4936415, in the IL10RA super-enhancer, conferring BD susceptibility. The protective G-allele of non-coding rs4936415 located inside an enhancer region of IL10RA promoted the enhancer activity and increased the expression of IL10RA.The risk C-allele is able to specifically bind NF-κB1 and, in turn, promotes enhancer activity of IL10RA. This subsequently leads to an increased expression of IL10RA. Low expression of IL-10RA suggests a relative deficiency of NF-κB1 in BD.